O COMPLEXO DE INSERÇÃO COMO FERRAMENTA SOCIAL PARA IMIGRANTES E REFUGIADOS EM VIDEIRA/SC - Grigolo, Cleiton; Pagnussat Camara, Inara (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
The increase in immigration flows to the Midwest region of Santa Catarina (Brazil) is an indicator of social and urban changes for some years. In line with the growing national index, the flows of immigrants and refugees from countries such as Haiti, Venezuela, Angola, and Congo are currently received in Videira / SC without specific infrastructure for housing and cultural insertion, making the process more difficult for adaptation and socioeconomic development. Demonstrating architecture as a social tool that creates opportunities is a central objective in this work, as well as a search for answers regarding habitability, future perspectives, existing infrastructure, methods that are already being used in other parts of the world, and other issues that are connected to cultural, economic, urban, and social spheres. The studied proposal seeks to support immigrants and refugees in the creation of an insertion complex: serving as temporary housing and offering a range of urban activities and services that provide a full circle in the search for the socio-economic development of the target users; offering activities and services related to culture, language, and customs brought by immigrants and providing the best conditions for inclusion in society. Another intention is to study strategies for reframing the characteristics linked to social architecture, seeking new ways, methods, investment possibilities, and ways of including the necessary infrastructure, in the search for a fair and economic architecture, one that demonstrates its need in today's society, fostering discussion on the immigration topic.